Same Voices, Other Tombs: Structures of Mexican Gothic - Djelal Kadir (Studies in 20th & 21st Century Literature, 1976)
The new Gothic may be explained in part as a consequence of a transition from an analogical to a metaphorical relationship between the corporeal and transcendent spheres of human experience. Irving Malin and, in a related effort, J. Douglas Perry delineate certain categories of themes, images, and narrative structures which define "new American Gothic" in contemporary fiction. Departing from Northrop Frye's observation that archetypes are basically a problem of structure rather than historical origin, and, that there may be archetypes of genres as well as of images, the present essay attempts to decipher certain paradigmatic categories and structures which reveal the presence of the Gothic genre in the contemporary Mexican novel. Carlos Fuentes' La muerte de Artemio Cruz and Juan Rulfo's Pedro Páramo serve as the source of the categories delineated in this study.
Keywords: Irving Malin; J. Douglas Perry; new American Gothic; contemporary fiction; Northrop Frye; Gothic genre; contemporary Mexican novel; Carlos Fuentes; Juan Rulfo; La muerte de Artemio Cruz; Pedro Páramo